Reputation, incitative mechanism in intermediation's function of mobiles bankers in sub-saharian Africa - (:unkn) unknown (My University, 1996)
The mobile banker's trade knows an important mutation. This one translates the primacy of financing on the collecte of savings, the first banker's trade. To face up to this evolution, mobiles bankers develop their brand image by building up a reputation of persons close relatives to theirs customers who can bring financing of which they would need. Reputation becomes incitative mechanism of mobiles bankers intermediation's fonction. This paper, develops the mechanism by which mobiles bankers build up their reputation, studies the impact of reputation's effect on the inter-temporal coordination of the intermediation's complementarity with formal financial system. The analysis of the mobile bankers new's behaviours is examined in the light of recent reputation's models.
Keywords: African Research